Employee Retention in the Era of Generation Z: A Bibliometric Study - Wijaya, Muhammad Nur Ilham; Yulianti, Praptini (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study analyzes Generation Z retention using a bibliometric approach. Data were obtained from Scopus, selecting 41 articles related to Generation Z and Retention. The findings indicate a growing trend in publications over the past few years. Network analysis reveals strong connections between Employee Retention, Psychology, Sustainability, and Talent Management, emphasizing the need for a multidisciplinary approach. Density visualization highlights a primary focus on employee management, while sustainability and the creative industry remain underexplored. This study concludes that Generation Z retention strategies should incorporate flexibility, work-life balance, values, and technology to align with the characteristics of this generation.